Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1158/0008-5472.can-03-1862
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface-Dependent Generation of Angiostatin4.5

Abstract: Angiostatin4.5 (AS4.5) is a naturally occurring human angiostatin isoform, consisting of plasminogen kringles 1-4 plus 85% of kringle 5 (amino acids Lys78 to Arg529). Prior studies indicate that plasminogen is converted to AS4.5 in a two-step reaction. First, plasminogen is activated to plasmin. Then plasmin undergoes autoproteolysis within the inner loop of kringle 5, which can be induced by a free sulfhydryl donor or an alkaline pH. We now demonstrate that plasminogen can be converted to AS4.5 in a cell memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…Although membrane-bound and secreted proteins are more likely to be cleaved and found in the circulation [12], our GO STAT analysis determined that most up-regulated and down-regulated proteins were involved in glycolysis, cytoplasm, cytosol and intracellular part. Proteins, such as heat shock proteins and actins, generally viewed as cytoplasmic, have been increasingly implicated in extracellular functions [13,14]. Eukaryotic protein secretion normally routes through the endoplasmatic reticulum (ER) and Golgi, ending up in a secretory vesicle fusing to the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Although membrane-bound and secreted proteins are more likely to be cleaved and found in the circulation [12], our GO STAT analysis determined that most up-regulated and down-regulated proteins were involved in glycolysis, cytoplasm, cytosol and intracellular part. Proteins, such as heat shock proteins and actins, generally viewed as cytoplasmic, have been increasingly implicated in extracellular functions [13,14]. Eukaryotic protein secretion normally routes through the endoplasmatic reticulum (ER) and Golgi, ending up in a secretory vesicle fusing to the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Individual plasminogen kringles and various subsets of kringle domains have angiostatin activity, and many are more potent angiogenesis inhibitors than the 38-kd fragment containing K 1-4 , which was originally identified as angiostatin (51)(52)(53). Thus, the K 1-3 , K 1-5 , and K 1-4.5 (kringles 1-4 plus 85% of kringle 5) fragments exhibit more antiangiogenic activity than K 1-4 (12,54,55). Remarkably, we detected the presence of several "angiostatins" in the SSc patient plasma, including the presence of a 25-kd form (lysine K 1-3 ).…”
Section: Discussionmentioning
confidence: 99%
“…A well-known high affinity ligand for DBP is the monomeric form of actin (Gactin), and plasma DBP serves as an extracellular scavenger for actin released from necrotic tissue (White and Cooke, 2000). Actin is the most prevalent intracellular protein, however, several investigators have reported actin on the extracellular face of the plasma membrane in lymphocytes and endothelial cells (Dudani et al, 2005;Petrini et al, 1983;Petrini et al, 1985;Wang et al, 2006;Wang et al, 2004). Reports have also shown that other cytoskeletal proteins are expressed on the cell surface (Moisan and Girard, 2006).…”
Section: Discussionmentioning
confidence: 99%